HUBUNGAN ANTARA MOTIVASI PERAWAT DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (HANDSCOON dan MASKER) DI INSTALASI RAWAT INAP RSUD dr. LOEKMONO HADI KUDUS - Kustriyani, Menik; Kharisa, Aji Susanti; Arifianto, Arifianto (Journal Of Holistic Nursing Science, 2018)
While doing their job as nurses, it is a must for the nurses to use PPE (PersonalProtective Equipment) based on the SOP which is established by the hospital. One of theinfluencing factors of the nursesâ obedience in using PPE is their motivations. Thepurpose of this study is to discover the relation between nurseâs motivation withobedience of using general precautions. This research is a non experimental quantitativeresearch which used cross sectional design. Using simple random sampling, there were153 nurses as the sample for this study. The instrument of this study were questionnairesand observation sheets. Rank Spearman Correlation Test was used in this research toanalyze the data.The result of Rank Spearman with p = 0,000 with the value of r = 0,507with positive correlation which also shows that nurses with higher motivation will alsohave higher obedience in using PPE. Conclusion: the higher the nurses motivation thehigher the adherence to the use of PPE.   Perawat dalam melakukan asuhan keperawatan harus menggunakan APD sesuai denganSOP yang telah ditetapkan oleh rumah sakit. Faktor yang mempengaruhi kepatuhanpenggunaan APD salah satunya adalah motivasi. Tujuan Penelitian ini adalah untukmengetahui hubungan antara motivasi perawat dengan kepatuhan penggunaan alatpelindung diri. Penelitian ini adalah penelitian kuantitatif yang merupakan penelitian nonexperimental dengan menggunakan desain cross sectional. Jumlah sampel penelitian inisebanyak 153 perawat dengan tehnik simpel random sampling. Instrumen penelitian inimenggunakan kuesioner dan lembar observasi. Analisa data menggunakan uji korelasiRank Spearman. Hasil uji Rank Spearman nilai p = 0,000 dengan nilai r = 0,507 arahkorelasi positif yang berarti semakin tinggi motivasi perawat maka semakin tinggikepatuhan penggunaan APD. Kesimpulan: semakin tinggi motivasi perawat makasemakin tinggi kepatuhan penggunaan APD.